Effect of Milwaukee brace on static and dynamic balance of female hyperkyphotic adolescents - Eshraghi, A.; Maroufi, N.; Sanjari, M.A.; Saeedi, H.; Keyhani, M.R.; Gholizadeh, H.; Abu Osman, Noor Azuan (2012)
Background: Biomechanical factors, such as spinal deformities can result in balance control disorders.Objectives: The purpose of this study was to examine the effect of bracing on static and dynamic balance control of hyperkyphotic female adolescents.Study Design: Clinical trial.Methods: A force platform was employed to record center of pressure (COP) parameters. Ten adolescents undergoing Milwaukee brace for hyperkyphosis and 14 normal subjects participated in the study. The COP data were collected with and without brace immediately on first day and after 120 days of continuous brace wear.Results: No significant difference was found in dynamic and static balance tests with and without brace on the first day (P > 0.05). After 120 days, the values of COP displacement in functional reach to the right and left for the hyperkyphotic adolescents when performing without brace enhanced significantly compared to the first day. The forward reach distance was not significantly different between the normal and hyperkyphotic subjects (P = 0.361); however, hyperkyphotic participants had significantly smaller reach distance in the functional reach to the right (21.88 vs. 25.56cm) and left (17.04 vs. 21.25cm).Conclusion: It might be concluded that bracing had a possible effect on improvement of dynamic balance performance, because the subjects could reach the target in dynamic reach tests with higher displacement in sagittal plane without losing their balance control.